2016
DOI: 10.15283/ijsc16020
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking the Neurogenic Potential of Mammalian Müller Glia

Abstract: Müller glia (MG) are the primary support cells in the vertebrate retina, regulating homeostasis in one of the most metabolically active tissues. In lower vertebrates such as fish, they respond to injury by proliferating and reprogramming to regenerate retinal neurons. In mammals, MG may also react to injury by proliferating, but they fail to initiate regeneration. The barriers to regeneration could be intrinsic to mammalian MG or the function of the niche that cannot support the MG reprogramming required for l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…However, this protective effect is opposed by the fact that the α 2 M*/LRP1 interaction also causes MGC activation during the proliferative stage inducing the up-regulation of GFAP 13 , which contribute to retinal function loss and neuronal cell death 42 . In this complex scenario, MGCs become particularly relevant due to their latent stem cell potential, positioning MGCs as excellent targets for regenerative therapies 4345 . In this regard, MGCs cultured under appropriate circumstances in vitro 46,47 can, when transplanted in vivo 46,47 , display an improved ability to migrate towards retinal injured sites.…”
Section: Discussionmentioning
confidence: 99%
“…However, this protective effect is opposed by the fact that the α 2 M*/LRP1 interaction also causes MGC activation during the proliferative stage inducing the up-regulation of GFAP 13 , which contribute to retinal function loss and neuronal cell death 42 . In this complex scenario, MGCs become particularly relevant due to their latent stem cell potential, positioning MGCs as excellent targets for regenerative therapies 4345 . In this regard, MGCs cultured under appropriate circumstances in vitro 46,47 can, when transplanted in vivo 46,47 , display an improved ability to migrate towards retinal injured sites.…”
Section: Discussionmentioning
confidence: 99%
“…However, the substantial differences in the genetic setup of hiPSCs and mature MGC likely contribute to the incapacity of the latter to regenerate PHRs during retina degeneration. The inability of MGC to regenerate the retina has been suggested to result from either intrinsic features of mammalian MGC or extrinsic properties of their “niche,” which interfere with the reprograming process of these cells (Xia and Ahmad, 2016). Analysis of cultured MGC from rd1 retinas revealed that their cell cycle was downregulated, compared to wt MGC.…”
Section: Discussionmentioning
confidence: 99%
“…Extrinsic and intrinsic factors participate in the activation process associated with Müller glial cells in retinal regeneration, including SHH ( 14 ), Notch ( 15 ), Wnt ( 16 , 17 ) and fibroblast growth factor ( 18 ) signaling pathways. Activation of these pathways, due to injury or exogenous ligands, induces a subset of Müller glial cells into the G1-S phase of the cell cycle ( 6 , 39 ). Our previous study indicated that SHH may promote the proliferation of Müller glial cells by increasing the expression of cyclin D1 and cyclin D3 ( 14 ).…”
Section: Discussionmentioning
confidence: 99%